Rethinking range ecology - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
If the 1980s were 'the lost decade' in African development then the use made of rangeland was high on the list of problem areas. The majority of ranching projects, range enclosures, community grazing schemes and resettlement of pastoralists are...